BINOLAPOR: Aplikasi Pelaporan Keamanan Dan Kerusakan Fasilitas Umum Desa Studi Kasus Desa Binorong Banjarnegara - Mia Anjani; Khalimaturofi’ah; Ferry Febrianto (CV. ITTC INDONESIA, 2025)
Binorong Village, Bawang District, Banjarnegara Regency, still faces challenges in reporting security issues and public facility damages, which are done manually through verbal or personal messages. This study aims to develop a web-based application to facilitate residents in reporting such issues. The research uses a qualitative approach with the Waterfall development model, system design using UML, implementation with the CodeIgniter framework and MySQL database, and testing through Black Box Testing and questionnaires. The results show that the application is feasible to use, as indicated by error-free Black Box Testing and average questionnaire scores of 4.1 from administrators and 3.9 from residents on a 5-point scale (categorized as feasible). This application helps residents report security and facility issues and assists village officials in monitoring and following up on incoming reports.